2012
DOI: 10.1016/j.matbio.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondins as key regulators of synaptogenesis in the central nervous system

Abstract: Thrombospondins (TSPs) are a family of large, oligomeric multidomain glycoproteins that participate in a variety of biological functions as part of the extracellular matrix (ECM). Through their associations with a number of binding partners, TSPs mediate complex cell-cell and cell-matrix interactions in such diverse processes as angiogenesis, inflammation, osteogenesis, cell proliferation, and apoptosis. It was recently shown in the developing central nervous system (CNS) that TSPs promote the formation of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 131 publications
4
143
0
3
Order By: Relevance
“…6). Several studies have demonstrated the importance of the TSP-1-a2d1 interaction in synaptogenesis; however, the mechanism by which the a2d1 ligands including TSP-1 participates in synaptogenesis remains unclear (Eroglu et al, 2009;Risher and Eroglu, 2012). Kurshan et al (2009) showed that a2d1 may act through cytoskeletal rearrangements, and regulation of the cytoskeleton is known to be important for synaptic spine formation.…”
Section: Discussionmentioning
confidence: 99%
“…6). Several studies have demonstrated the importance of the TSP-1-a2d1 interaction in synaptogenesis; however, the mechanism by which the a2d1 ligands including TSP-1 participates in synaptogenesis remains unclear (Eroglu et al, 2009;Risher and Eroglu, 2012). Kurshan et al (2009) showed that a2d1 may act through cytoskeletal rearrangements, and regulation of the cytoskeleton is known to be important for synaptic spine formation.…”
Section: Discussionmentioning
confidence: 99%
“…PDZ domains are protein-interaction domains that are concentrated in the postsynaptic density and regulate synaptic transmission (Kim and Sheng, 2004). Furthermore, the N-termini of BAIs encodes thrombospondin type 1 repeats (TSRs), which regulate synaptogenesis and neural development (Adams and Tucker, 2000;Risher and Eroglu, 2012). These TRS repeats act as major interacting regions for BAI interaction partners, including the C1q-like proteins (Bolliger et al, 2011), which are highly expressed in the CNS and aid in synapse formation (Yuzaki, 2010).…”
Section: Reviewmentioning
confidence: 99%
“…Regulation of angiogenesis and cancer progression (12), regulation of inflammation (8, 13-16), modulation of immune response (17, 18), formation of myotendinous junctions (19), maintenance of the myocardium integrity and function (20-27), regulation of fibrosis (28), and synaptogenesis (29) are just a few examples of their roles in physiology and pathology. To participate in the critical physiological processes, TSPs have to be present in the right location at the right time.…”
Section: Introductionmentioning
confidence: 99%